Anti-GP2 IgA autoantibodies are associated with poor survival and cholangiocarcinoma in primary sclerosing cholangitis - Jendrek, Sebastian Torben; Gotthardt, Daniel; Widmann, Laila Virginia; Weiss, Karl Heinz; Schemmer, Peter (Gut, 2017)
Objective Pancreatic autoantibodies (PABs), comprising antibodies against glycoprotein 2 (anti-GP2), are typically associated with complicated phenotypes in Crohn's disease, but have also been observed with variable frequencies in patients with UC. In a previous study, we observed a high frequency of primary sclerosing cholangitis (PSC) in patients with anti-GP2-positive UC. We therefore aimed to characterise the role of anti-GP2 in PSC. Design In an evaluation phase, sera from 138 well-characterised Norwegian patients with PSC were compared with healthy controls (n=52), and patients with UC without PSC (n=62) for the presence of PABs by indirect immunofluorescence. Further, 180 German patients with PSC served as a validation cohort together with 56 cases of cholangiocarcinoma without PSC, 20 of secondary sclerosing cholangitis (SSC) and 18 of autoimmune hepatitis. Results Anti-GP2 IgA specifically occurred at considerable rates in large bile duct diseases (cholangiocarcinoma=36%, PSC and SSC about 50%). In PSC, anti-GP2 IgA consistently identified patients with poor survival during follow-up (Norwegian/German cohort: p Log Rank=0.016/0.018). Anti-GP2 IgA was associated with the development of cholangiocarcinoma in both PSC cohorts, yielding an overall OR of cholangiocarcinoma in patients with anti-GP2 IgA-positive PSC of 5.0 (p=0.001). Importantly, this association remained independent of disease duration, bilirubin level and age. Conclusions Anti-GP2 IgA can be hypothesised as a novel marker in large bile duct diseases. In particular, in PSC, anti-GP2 IgA identified a subgroup of patients with severe phenotype and poor survival due to cholangiocarcinoma. Anti-GP2 IgA may therefore be a clinically valuable tool for risk stratification in PSC.